2015
DOI: 10.1038/ncomms7655
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 regulates the dynamics of its cochaperone Sti1 and the transfer of Hsp70 between modules

Abstract: The cochaperone Sti1/Hop physically links Hsp70 and Hsp90. The protein exhibits one binding site for Hsp90 (TPR2A) and two binding sites for Hsp70 (TPR1 and TPR2B). How these sites are used remained enigmatic. Here we show that Sti1 is a dynamic, elongated protein that consists of a flexible N-terminal module, a long linker and a rigid C-terminal module. Binding of Hsp90 and Hsp70 regulates the Sti1 conformation with Hsp90 binding determining with which site Hsp70 interacts. Without Hsp90, Sti1 is more compact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 56 publications
(86 reference statements)
7
88
0
Order By: Relevance
“…Our parallel experiments testing the Hsp70/Hop interaction (Fig. 5C) supported previous results showing that high affinity interaction of these proteins is mediated by TPR1/TPR2B accommodation of EEVD motif only, independent of Hsp70 conformation (15,61,63). Nevertheless, additional low affinity contacts of Hsp70 and Hop suggested elsewhere (3,5,18,60,68) might have remained undetected by our methods.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our parallel experiments testing the Hsp70/Hop interaction (Fig. 5C) supported previous results showing that high affinity interaction of these proteins is mediated by TPR1/TPR2B accommodation of EEVD motif only, independent of Hsp70 conformation (15,61,63). Nevertheless, additional low affinity contacts of Hsp70 and Hop suggested elsewhere (3,5,18,60,68) might have remained undetected by our methods.…”
Section: Discussionsupporting
confidence: 90%
“…7B). Because the Hsp70/ Hop complex has a 1:1 stoichiometry (63) and TPR1/TPR2B domains were previously described as redundant (61) but differentially regulated (15,63) binding sites for the C-terminal motif of Hsp70, our results provide structural evidence for random and individual Hsp70 binding to each one of these domains. Conversely, Hop binding does not influence the level of deuterium exchange in Hsp70 protein, including peptide 533-543 (Fig.…”
Section: Hsp70 Allostery and Chaperone/co-chaperone Interactionsmentioning
confidence: 71%
“…The recent visualization of the eukaryotic Hsp90-Hsp70-Hop-client complex as well as earlier biochemical work from many groups suggests a mechanism for substrate transfer from Hsp70 to Hsp90 19,2830,39,40 . In the current model, the Hsp70 cochaperone, Hsp40, likely presents the client to Hsp70 and stabilizes the interaction between the client and Hsp70 prior to the binding of Hsp70 to Hop and Hop to Hsp90 2830 .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear magnetic resonance spectroscopy demonstrated that DP2 does not interact directly with purified HSP90 and HSP70, but it makes contacts with the TPR2B domain of STIP1 [5, 32]. DP2 domain forms a rigid C-terminal module with TPR2A and TPR2B domains [5, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear magnetic resonance spectroscopy demonstrated that DP2 does not interact directly with purified HSP90 and HSP70, but it makes contacts with the TPR2B domain of STIP1 [5, 32]. DP2 domain forms a rigid C-terminal module with TPR2A and TPR2B domains [5, 32]. Pull-down experiments with isotopically-labeled STIP1 and rabbit reticulocyte lysate have shown that the ability to bind HSP70 is reduced when STIP1 has a truncated or mutant DP2 domain [33-35].…”
Section: Discussionmentioning
confidence: 99%